The Effect of Electronic Word of Mouth and Celebrity Endorser Through Brand Trust on Repurchasing Interests of Lip Cream Make Over Products - Tuffa Hati Berliana; Ra Nurlinda (PT FORMOSA CENDEKIA GLOBAL, 2022)
Many women think that the use of masks, can cause the lipstick used to always stick to the mask and leave a mark so that the lipstick they wear can't last long and reduce their makeup look unattractive. In these conditions Make Over created its newest lipstick formula, Lipcream Powerstay Transproof where this type of lipstick can be used even if you wear a mask, because the texture of this lipstick can last for 14 hours on the lips even if you drink it. This study examines the direct effect of electronic word of mouth and celebrity endorser on repurchase interest with the brand trust variable as the intervening variable. Premiere data was collected using a survey method by distributing questionnaires to respondents who had purchased and used MakeOver lip cream. The questionnaires collected were 145 respondents, the data was then processed by path analysis method. Based on the results of research analysis there is a direct influence between electronic word of mouth on brand trust, there is a direct influence between electronic word of mouth, celebrity endorser, and brand trust on repurchase interest, but there is no direct influence of celebrity endorser on brand trust. Brand trust is not an intervening variable between electronic word of mouth variables and repurchase interest